Pengaruh Model Pembelajaran Team Quiz terhadap Motivasi Belajar Siswa pada Pelajaran IPS Kelas VII di MTsN 2 Tulungagung - Alifah Ilyana; Agus Eko Sujianto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the effect of the team quiz learning model on student learning motivation in social studies class VII at MTsN 2 Tulungagung. This study uses an associative type quantitative research approach. This study sets four problem formulations where the motivation variable is reduced to four indicators, namely attention, relevance, confidence, and satisfaction. The sample used in this study consisted of 32 class B students and 32 class C students. The technique used in this study was purposive sampling. The results of the study showed that the team quiz learning model had a significant effect on student attention with a sig value. (2-tailed) 0.003<0.05. Team quiz learning has a significant effect on the relevance of student learning with a sig value. (2-tailed) 0.023<0.05. Team quiz learning has a significant effect on student confidence with a sig value. (2-tailed) 0.000<0.05. Team quiz learning has a significant effect on student satisfaction with a sig value. (2-tailed) 0.030<0.05. Thus it can be concluded that the team quiz learning model has a significant effect on learning motivation which is reduced to four indicators, namely attention, relevance, confidence, and student satisfaction.